Cover crop–based, rotational no‐till management tactics influence crop performance in organic transition within the Mid‐Atlantic United States. (11th October 2021) - Wallace, John M.; Barbercheck, Mary E.; Curran, William; Keene, Clair Lynn; Mirsky, Steven Brian; Ryan, Matthew; VanGessel, Mark
Abstract: Reducing the intensityand frequency of tillage in an organic grain system requires an emphasis on utilizing ecological processes to manage pests and fertility. Cover crop–based, organic rotational no‐till (CCORNT) corn ( Zea mays L.) and soybean [ Glycine max (L.) Merr.] production systems utilize cover crop surface mulch as the primary within‐season weed control tactic. Winter‐sown cereal rye ( Secale cereale L.) was grown preceding soybean and hairy vetch ( Vicia villosa Roth) mixtures before corn. We conducted a 3‐yr cropping systems experiment in Delaware, Maryland, and Pennsylvania to evaluate crop management (planting date) and integrated weed management (IWM) tactics for CCORNT corn and soybean production in a corn–soybean–winter wheat ( Triticum aestivum L.) rotation during the transition to organic. Corn and soybean yields were sensitive to planting date, but optimal planting dates differed among locations. Delayed cover crop termination did not consistently increase total cover crop biomass production or reduce weed biomass levels. High‐residue cultivation reduced total weed biomass across locations, but this IWM tactic produced variable results on cash crop yields. Total weed biomass was negatively correlated to soybean yields but did not influence corn yields. At the Pennsylvania location, delaying corn planting dates was positively correlated with predatory athropod activity‐density, which was positively correlated with corn populations. Assessment of CCORNT practices on short‐term soil health indicators (labile carbon, aggregate stability, entomopathogenic fungi) at the Pennsylvania location produced variable results. Adaptive pest management strategies will need to be used in CCORNT systems within the Mid‐Atlantic United States. Core Ideas: Corn and soybean yield‐limiting factors differed across Mid‐Atlantic locations. High‐residue cultivation decreased weed biomass but had variable effects on yield. Cover crop biomass was not consistently correlated with lower weed biomass. Planting date influenced predatory arthropod activity‐density in corn. Adaptive pest management tactics are needed to balance management tradeoffs.